The Buzz of Drinking on the Wing in Echolocating Bats. (28th December 2015) - Russo, Danilo; Ancillotto, Leonardo; Cistrone, Luca; Korine, Carmi
Abstract: Bats broadcast rapid sequences of echolocation calls, named 'drinking buzzes', when they approach water to drink on the wing. So far this phenomenon has received little attention. We recorded echolocation sequences of drinking bats for 12 species, for 11 of which we also recorded feeding buzzes. Based on the different sensorial tasks faced by feeding and drinking bats, we hypothesize that the drinking buzz structure will differ from that of feeding buzzes since unlike the latter drinking buzzes are not designed to detect and track mobile prey. We demonstrated that drinking buzzes are structurally different from feeding buzzes. We show that the buzz‐II phase common in feeding buzzes is absent in drinking buzzes; that is, call frequency is not lowered to broaden sonar beam since the task of drinking does not imply tracking fast‐moving targets. This finding indirectly confirms the role of buzz II in feeding buzzes. Pulse rate in drinking buzzes is also lower than in feeding buzzes, as predicted since the high pulse rate typical of feeding buzzes is important to update rapidly the relative location of moving targets. The most likely function of drinking buzzes is to guide a safe drinking manoeuvre, similar to 'landing buzzes' broadcast when bats land on the ground.